Environmental implications of the Brazilian tax reform on household consumption - Bícego, Samuel Pedro (2025)
Climate change has increasingly been recognized as a challenge to global economic development, with impacts that are heterogeneously distributed across regions. Effective climate policies require accurate emissions data from different sources-especially in Brazil, where over 70% of Greenhouse Gas (GHG) emissions come from agriculture and land-use change. Using comprehensive data on the carbon footprint of Brazilian products, this paper evaluates Brazil\'s recent tax reform, which replaces cascading taxes with a unified Value-Added Tax (VAT) and introduces a Selective Tax (ST) on products harmful to health or the environment. Our analysis draws on two main datasets: (i) carbon footprint estimates for 128 products, including satellite-based land-use emissions; and (ii) detailed household consumption data from Brazil\'s National Expenditure Survey (POF). Simulation results suggest that the reform may increase household GHG emissions in Brazil by 3.12%, largely due to exemptions granted to high-carbon-intensity foods. However, applying the proposed ST on emissions-intensive goods could offset this effect. Welfare effects vary by scenario. Environmental taxes, when accompanied by well-designed revenue recycling mechanisms, are capable of reducing emissions without compromising food security and at relatively low social costs. The distributive analysis highlights a dilemma: low-income households benefit from exemptions and cashback policies, which improve their welfare and expand food consumption but also raise their emissions; whereas high-income households reduce emissions associated with non-food items, though they continue to account for a substantial share of total emissions. These results provide evidence to better align tax policy with climate goals, underscoring the importance of more targeted environmental taxation and socially just compensation mechanisms.